Braveheart - Gibson, Mel.; Ladd, Alan, 1937-; Davey, Bruce; Wallace, Randall; Marceau, Sophie, 1966-; McGoohan, Patrick, 1928-2009.; Icon Productions; Ladd Company; Paramount Pictures Corporation (Hollywood, CA : Paramount, 2006)
William Wallace is a bold Scotsman who used the steel of his blade and the fire of his intellect to rally his countrymen to liberation.
Based on the book by Randall Wallace.
Originally released as a motion picture in 1995.
Special features include: Interactive menus ; scene selection ; 2 theatrical trailers ;commentary by Mel Gibson ; A filmmaker's pasison : the making of Braveheart.
Director of photography, John Toll ; editor, Steven Rosenblum ; music, James Horner.
Mel Gibson, Sophie Marceau, Patrick McGoohan, Catherine McCormack.
MPAA rating: R.
Keywords: Wallace, William, -- Sir, -- -1305 -- Drama; Wallace, William, -- Sir, -- -1305 -- Drama; Wallace, William, -- Sir, -- -1305; 1297 - 1304; Insurgency -- Scotland -- Drama; Historical films; Feature films; Video recordings for the hearing impaired; Insurgency -- Scotland -- Drama; Feature films; Historical films; Insurgency; Video recordings for the hearing impaired; Scotland -- History -- Wallace's Rising, 1297-1304 -- Drama; Scotland -- History -- Wallace's Rising, 1297-1304 -- Drama; Scotland; Drama; History